International project management - Koster, Kathrin (London : SAGE, 2009)
This volume links the key elements of cross-cultural management and the particularities of an international context, with the tools and techniques of project management. Key features include: a wide variety of examples and illustrations, student excercises and review questions and detailed further reading.
Introduction to international project management -- The context of international projects in terms of organizational strategy and culture -- Defining the international project -- Managing risk and uncertainty in an international project -- Planning the international project in terms of time, cost, and quality -- Organizing the international project -- Implementing and controlling international projects -- Leading international projects -- Communicating in international projects -- Co-operating in international projects -- Learning in and learning from international projects.
Includes bibliographical references (p. [343]-353) and index.
Keywords: Project management; International business enterprises -- Management